Efficient Cell-Clustering Algorithm for Inter-Cluster Interference Mitigation in Network MIMO Systems - Moon, Jung-Min; Cho, Dong-Ho (IEEE communications letters, 2011)
Coordinated transmission in network MIMO systems, in which a set of access points form a cluster and serve each user in the network, is currently the subject of a great deal of research effort. We propose a cell-clustering algorithm that aims at finding the efficient configuration of the clusters to increase the sum-rate of the users. Through simulation, we observe the improved performance of the proposed algorithm in terms of the sum-rate and the outage probability.